2020
DOI: 10.21203/rs.2.18574/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinctions between sex and time in patterns of DNA methylation across puberty

Abstract: Background: There are significant sex differences in human physiology and disease; the genomic sources of these differences, however, are not well understood. During puberty, a drastic neuroendocrine shift signals physical changes resulting in robust sex differences in human physiology. Here, we explore how shifting patterns of DNA methylation may inform these pathways of biological plasticity during the pubertal transition. In this study we analyzed DNA methylation (DNAm) in saliva at two time points across t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Furthermore, regions experiencing changes in methylation status in both sexes show changes with higher magnitude in females 24 . In contrast, other studies on pre-and post-pubertal subjects found limited differences in DNA methylation patterns between sexes 23,25 . These inconsistencies may be due to age differences between studies and could be further investigated by employing a study design that focuses on all pubertal developmental stages rather than comparing pre-and post-pubertal stages only.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Furthermore, regions experiencing changes in methylation status in both sexes show changes with higher magnitude in females 24 . In contrast, other studies on pre-and post-pubertal subjects found limited differences in DNA methylation patterns between sexes 23,25 . These inconsistencies may be due to age differences between studies and could be further investigated by employing a study design that focuses on all pubertal developmental stages rather than comparing pre-and post-pubertal stages only.…”
Section: Introductionmentioning
confidence: 66%
“…Previous studies of DNA methylation changes between pre-and post-puberty in females found overrepresentation of genes involved in immune and inflammatory responses 24,25,27 , reproductive hormone signaling 24 , and other physiological changes related to growth and development 26 . Our results allowed a more fine-grained insight into the changes in the immune system that accompany sexual maturation of females.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Sex differences in DNAm are expected on the X chromosome in humans due to X chromosome inactivation (Hall et al, 2014;Duncan et al, 2018). However, sex differences in DNAm have also been reported on autosomal chromosomes in numerous tissues including blood (7,(11)(12)(13), buccal cells (14,15), the prefrontal cortex (16), and the placenta (17,18). The number of differentially methylated sites ranged from a few hundred to nearly ten thousand in these studies, depending on the tissue, DNAm array, and available sample sizes.…”
Section: Introductionmentioning
confidence: 89%